2015
DOI: 10.1007/s10773-015-2741-9
|View full text |Cite
|
Sign up to set email alerts
|

Quantum Games under Decoherence

Abstract: Quantum systems are easily influenced by ambient environments. Decoherence is generated by system interaction with external environment. In this paper, we analyse the effects of decoherence on quantum games with Eisert-Wilkens-Lewenstein (EWL) (Eisert et al., Phys. Rev. Lett. 83(15), 3077 1999) and Marinatto-Weber (MW) (Marinatto and Weber, Phys. Lett. A 272, 291 2000) schemes. Firstly, referring to the analytical approach that was introduced by Eisert et al. (Phys. Rev. Lett. 83(15), 3077 1999), we analyse th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
5
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(6 citation statements)
references
References 44 publications
1
5
0
Order By: Relevance
“…has been represented pictorially by Figure 1. Figure 1(a) shows the distribution of Alice's payoff at t = 0, which is similar to Eisert et al [1] and that after t = 1000 is shown by Figure 1(b), which is consistent with Huang and Qiu [6]. The Nash equilibrium ( Q, Q) disappears as the time step runs from 0 to 1000.…”
Section: Results and Analysissupporting
confidence: 83%
“…has been represented pictorially by Figure 1. Figure 1(a) shows the distribution of Alice's payoff at t = 0, which is similar to Eisert et al [1] and that after t = 1000 is shown by Figure 1(b), which is consistent with Huang and Qiu [6]. The Nash equilibrium ( Q, Q) disappears as the time step runs from 0 to 1000.…”
Section: Results and Analysissupporting
confidence: 83%
“…The effect of other types of quantum noise [16] will be taken into account in future work. In particular that of phase-damping, structurally close to amplitude-damping as both damping noises have the same K 1 Kraus operator, deferring in K2=false(.2em0.333em000μfalse) with phase damping.…”
Section: The Classic and Quantum Samaritan’s Dilemmamentioning
confidence: 99%
“…Let us remark that only amplitude-damping quantum noise will be under scrutiny in this study. The effect of other types of quantum noise [ 16 ] will be taken into account in future work. In particular that of phase-damping, structurally close to amplitude-damping as both damping noises have the same K 1 Kraus operator, deferring in with phase damping.…”
Section: The Classic and Quantum Samaritan’s Dilemmamentioning
confidence: 99%
See 1 more Smart Citation
“…When dealing with real-world implementations of quantum systems, noise and decoherence must be taken into account to some extent in the theoretical model, quantum games are no exception [32][33][34]. In particular, a noisy version of Flitney and Abbot's Monty Hall quantum game was analyzed back in 2010 [35].…”
Section: Introductionmentioning
confidence: 99%